Relationship between Hedonic Hunger and Health Interest on Habit and Sodium Intake Patterns in Food Consumption - Imam Santoso; Susinggih Wijana; Afita Ismawati; Wenny Bekti Sunarharum (International Journal of Food Science)
Many people are motivated to eat healthily but find it difficult to override established and less healthy habits. Habits, by their nature, are unconscious and cued by the environment, thus making them powerful determinants of behavior. This study examined how hedonic hunger and health interest are related to habit and whether sodium consumption is mediated by hedonic hunger, health interest, and habit. A total of 117 students of Universitas Brawijaya took part in the study. Data analysis were done using Partial Least Square (PLS) and a semi-quantitative food frequency questionnaire (SQ-FFQ). PLS was used to analyze the influence of the relationship between independent and dependent variables. SQ-FFQ was used to determine sodium intake in grams/day. The average sodium intake in this study was 2.47 grams/day. This analysis shows that hedonic hunger and health interest had a significant impact on health habits but not on sodium intake.